Dry anaerobic digestion treatment potential for the organic fraction of municipal solid waste in Brazil and Mexico - Silva Martínez, Rodolfo Daniel (2021)
Anaerobic Digestion (AD) technologies have been developed and implemented in Brazil and Mexico to treat the organic fraction of municipal solid waste (OFMSW). However, they are still far away to significantly contribute to treating the ever-increasing waste volumes in the region and supply the regional energy demand, recuperate nutrients, and meet national carbon emission goals. This study aims to determine the feasibility of implementing AD, and more specifically dry anaerobic digestion (DAD) technologies, to treat the OFMSW evaluating the technical and environmental benefits and advantages these technologies offer, and secondly to propose the policy guidelines for implementing and disseminating AD technologies based on the existing regulatory framework in Brazil and Mexico. For this purpose, the research uses mixed methods research (MMR). It firstly performs an environment and resource use analysis to compare two case studies in Brazil: A wet anaerobic digester in Foz de Iguaçu and a dry anaerobic digester localized in Rio de Janeiro. This analysis includes an assessment of the water, material, and nutrients flow, energy efficiency, and mitigation of greenhouse gas emissions (GHG) as the most relevant categories, seeking the most efficient technology. A literature and public policy review and a series of interviews with researchers and public policy specialists to identify the limitations, challenges, and opportunities to apply AD from a governmental perspective complemented the case study analysis. The results indicate that even when the wet anaerobic digestion (WAD) system offers various advantages of water and resource savings, energy generation, and CO2eq emissions savings, there is a notable significant higher efficiency of the DAD system. (1) It utilizes less water throughout its processes; (2) it produces almost 2.5 times more solid digestate or biofertilizer; (3) it has significant energy efficiency, utilizing internally less energy of the biogas produced; and (4) it also presents a more significant GHG mitigation potential. Moreover, as for the policy analysis and interviews, according to this research findings, some of the detected main challenges in both countries are presented due to: (1) landfill and dumpsites overuse; (2) lack of waste segregation systems; (3) lack of knowledge or interest in AD technologies; (4) low education and social training in the field; (5) diverse economic factors; (6) lack of regulatory framework and infrastructure for biogas/biomethane; and (7) public policy deficiencies. Thus, this study resulted in a series of policy guidelines and recommendations that may serve to face these challenges and develop a national political plan to implement large-scale AD projects to treat the OFMSW; these may assist decision makers to prepare and implement new legislation and reforms to build more specific and coercive measures to overcome the challenges and for the adequate treatment of OFMSW with biodigesters. Ultimately, the crucial need to implement and disseminate biodigesters as the proper treatment of the OFMSW arises from the need to mitigate the environmental, social, and public health impacts caused by traditional practices of disposal of organic waste in dumps sites or sanitary landfills. This research proves that DAD can remarkably contribute to this task offering tangible diverse benefits to society and the environment.